RADIOFREQUENCY ABLATION (RFA) AS AN EFFECTIVE TREATMENT MODALITY FOR INSULINOMA - L, Deviga; SW, Lim; ZQ, Wong; AS, Nordashima; K, Nor Azmi; S, Norlela (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Insulinoma is the commonest type of functional neuroendocrine tumour involving the pancreas. Complete surgical removal has been the primary form of treatment, however, of late newer forms of treatment modalities are being utilised in place of surgery. We describe a case of insulinoma who was successfully treated with radiofrequency ablation (RFA). RESULTS A 53-year-old lady presented with recurrent hypoglycaemic symptoms over a 2-month period with blood glucose readings ranging from 2.6-3.9mmol/L. Her symptoms occurred following prolonged fast which were immediately relieved by food intake, fulfilling the criteria of Whipple’s triad. During her hospital stay, she had symptomatic fasting hypoglycaemia with a blood glucose of 2.1mmol/L associated with elevated C-peptide and insulin levels together with the absence of blood ketones. In addition she had normal IGF-1 and cortisol levels. Computed Tomography (CT) of the abdomen showed a small enhancing lesion at body of the pancreas measuring 1.6x1.4 cm which was confirmed by a subsequent Endoscopic ultrasound (EUS) revealing a 1 x 0.3 x 0.8 cm pancreatic lesion. Endoscopic fine needle aspiration revealed a pancreatic neuroendocrine tumour which stains for Synaptophysin and Chromogranin. However, both the Chromogranin A and 24-hour urine 5-Hydroxyindoleacetic Acid (HIAA) were within normal range. Subsequently she underwent RFA under EUS guidance. Following the procedure her blood glucose normalised ranging between 5.3-5.7 mmol/L. She was able to wean off the diaxozide that was used to treat the hypoglycaemia prior to procedure. Surveillance CT scan of the abdomen performed a month later showed a mild regression of the tumour size (1.4 x 1.4 cm). CONCLUSION We believe this is the first reported use of RFA under EUS guidance in the treatment of insulinoma in this country. The use of this less invasive treatment modality heralds a new dimension in the management of pancreatic tumours.